Focal Predominant Forms of Posthypoxic Action Myoclonus. Issue 4 (29th January 2016) - Gasca‐Salas, Carmen; Lang, Anthony E.
Abstract: Chronic posthypoxic action myoclonus is usually recognized as multifocal or generalized and, in most cases, causes severe disability. It is also commonly associated with other neurological symptoms, such as ataxia. We report two cases of focal predominant postanoxic action myoclonus and review the limited relevant literature. The first case presented with action and stimulus sensitive myoclonus in the lower limbs that caused him limited disability. He had not received any diagnosis in almost 2 years. The second patient exhibited predominantly focal facial myoclonus, although she was more limited by dysphasia and hemiplegia as a consequence of an ischemic stroke. Both patients responded to antiepileptic drugs. We found 9 of 159 previously reported cases with this focal distribution. Physicians should be aware of this limited phenotype given that the unusual focal nature of the movements may result in incorrect diagnosis and treatment.